Effect of sex-sorting and cryopreservation on the post-thaw sperm quality of Iberian red deer spermatozoa - Anel-López, L; García-Álvarez, O; Parrilla, I; Del Olmo, D; Maroto-Morales, A; Fernandez-Santos, M R; Ortiz, J A; Soler, A J; Martínez, E M; Vazquez, J M; Garde, J J (Theriogenology, 2017)
This study investigated the effect of sex-sorting and cryopreservation on post-thaw characteristics and fertility of red deer (Cervus elaphus) sperm for the first time. Semen was collected by electroejaculation from 10 mature stags during the breeding season, and each ejaculate split into four experimental groups: Bulk sorted spermatozoa, sorted but not sexed (BSS); sorted high purity X-spermatozoa (XSS); sorted high purity Y-spermatozoa (YSS); and, control non-sorted spermatozoa (NS). Following, all samples were frozen over liquid nitrogen. Two straws per stag and sample type were analyzed immediately post-thaw and following a 2-h incubation period at 37 °C. Post-thaw total motility (TM) as assessed by CASA was not different (P < 0.05) among NS, BSS and YSS sperm. For XSS, post-thaw TM was lower (39%, P < 0.05) than that for NS (54%) or BSS (50%), but similar (P > 0.05) to that of YSS (47%) sperm. The percentage of apoptotic spermatozoa as assessed by PI/YO-PRO-1 and flow cytometry analysis, was higher (17%, P ≤ 0.05) for XSS sperm than NS (12%), BSS (13%) and YSS (14%) sperm. Following incubation there were no differences (P > 0.05) in TM or percent apoptosis among treatments. Post-thaw chromatin stability calculated as the DNA fragmentation index (%DFI) was similar among treatments; following incubation %DFI increased in all except YSS, which displayed the lowest value (P < 0.05). Artificial insemination of synchronized hinds yielded 44, 52 and 62% delivery rates for YSS, NS and standard frozen-thawed sperm, respectively (P < 0.05). Notably, 93 and 55% of fawns born were males for the YSS and NS spermatozoa, respectively (P < 0.05). In summary, Y-sorted sperm displayed acceptable post-thaw sperm evaluation parameters and the expected offspring sex ratio. More studies are needed to understand the source of sperm damage that may compromise the fertility of Y-sorted red deer sperm.
Keywords: Animals; Cryopreservation; Insemination, Artificial; spermie; průtoková cytometrie; DNA Fragmentation; fragmentace DNA; Spermatozoa; Semen Preservation; Sex Ratio; Flow Cytometry; Deer; motilita spermií; kryoprezervace; Male; poměr pohlaví; umělá inseminace; předvýběr pohlaví; Sex Preselection; Sperm Motility; zvířata; mužské pohlaví; uchování spermatu; vysoká zvěř